Unidirectional and sustained delivery of the proresolving lipid mediator resolvin D1 from a biodegradable thin film device. Issue 1 (23rd August 2016) - Lance, Kevin D.; Chatterjee, Anuran; Wu, Bian; Mottola, Giorgio; Nuhn, Harald; Lee, Phin Peng; Sansbury, Brian E.; Spite, Matthew; Desai, Tejal A.; Conte, Michael S.
Abstract: Resolvin D1 (RvD1) belongs to a family of endogenously derived proresolving lipid mediators that have been shown to attenuate inflammation, activate proresolution signaling, and promote homeostasis and recovery from tissue injury. In this study we present a poly(lactic‐ co ‐glycolic acid) (PLGA) based thin‐film device composed of layers of varying ratios of lactic and glycolic acid that elutes RvD1 unidirectionally to target tissues. The device demonstrated sustained release in vitro for 56 days with an initial burst of release over 14 days. The asymmetric design of the device released 98% of RvD1 through the layer with the lowest molar ratio of lactic acid to glycolic acid, and the remainder through the opposite side. We validated structural integrity of RvD1 released from the device by mass spectrometry and investigated its bioactivity on human vascular endothelial (EC) and smooth muscle cells (VSMC). RvD1 released from the device attenuated VSMC migration, proliferation, and TNF‐α induced NF‐κB activation, without evidence of cytotoxicity. Delivery of RvD1 to blood vessels was demonstrated ex vivo in a flow chamber system using perfused rabbit aortas and in vivo in a rat carotid artery model, with the devices applied as an adventitial wrap. Our results demonstrate a novel approach for sustained, local delivery of Resolvin D1 to vascular tissue at therapeutically relevant levels. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 31–41, 2017.